A DETERMINATION OF FUEL CONSUMPTION FOR DRYING COTTON RAW MATERIALS: Determination of fuel consumption for drying cotton raw materials - Dedaxanov, Akranjon (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2025)
In cotton gins, drying cotton before cleaning it is of great importance. Since cotton drying is associated with thermal energy, determining the fuel used to dry cotton raw materials is the basis of economic efficiency.